2011
DOI: 10.1007/s10592-011-0198-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of chloroplast DNA variation in Cycas debaoensis (Cycadaceae): conservation implications

Abstract: Climate changes during glacial periods have had significant effects on the current distribution of plant species. Palaeontologial data suggest that modern cycads originated in southwest China. Cycas debaoensis (Cycadaceae) is an endangered species restricted to a small area of southwest China. This species has been classified into two types: sand and karst, according to the soil matrix they grow on. To determine the locations of its glacial refugia and its genetic structure, we examined chloroplast sequence va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 66 publications
(60 reference statements)
3
44
0
3
Order By: Relevance
“…Thus, we can compare the genetic diversity of C. guizhouensis with other Asian Cycas species using the similar molecular markers. Cycas guizhouensis had higher genetic diversity (Tables 2, S2 and S3) than C. debaoensis 27, but had slightly lower genetic diversity than C. simplicipnna 9 and C. multipinnata 10. cpDNA-based studies on 170 plant species revealed a mean value of H T  = 0.6747, while H T estimated from C. guizhouensis by four cpDNA was 0.841 which implied that C. guizhouensis had a high level of genetic diversity.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Thus, we can compare the genetic diversity of C. guizhouensis with other Asian Cycas species using the similar molecular markers. Cycas guizhouensis had higher genetic diversity (Tables 2, S2 and S3) than C. debaoensis 27, but had slightly lower genetic diversity than C. simplicipnna 9 and C. multipinnata 10. cpDNA-based studies on 170 plant species revealed a mean value of H T  = 0.6747, while H T estimated from C. guizhouensis by four cpDNA was 0.841 which implied that C. guizhouensis had a high level of genetic diversity.…”
Section: Discussionmentioning
confidence: 93%
“…Distinct demographics were detected in different plant taxa as a result of glacial and interglacial periods. Gymnosperm species, such as Taxus wallichiana 53, Cycas revoluta , and Cycas taitungensis 54, have experienced population expansions during the most recent glacial period, while Cycas debaoensis 27, Cycas simplicipinna 9 and Cycas multipinnata 10 have experienced population contractions. In this study, four cpDNA, three nuclear genes and 13 microsatellites generated inconsistent results for the demography of C. guizhouensis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Either through the lens of 'classical' population genetics (Gonz alez-Astorga et al, 2003b, 2005, 2006 or through phylogeography (Huang et al, 2001;Chiang et al, 2009;Kyoda & Setoguchi, 2010;Zhan et al, 2011;Guti errez-Ortega, Kajita & Molinar-Freaner, 2014;Nolasco-Soto et al, 2015), the results of further work in this direction will allow the construction of ancestor-descendant hypotheses involving known populations, as well as the assessment of demographic history and genetic differentiation between these populations. In accordance with our population-genetic research programme, evolutionary inferences derived from these phylogeographical interventions will constitute the starting point in species recognition and circumscription.…”
Section: Discussionmentioning
confidence: 99%
“…2 a y c). Debido a la organización estructural conservada del ADNcp en plantas superiores, sumado al reducido flujo génico mediado por semillas, pueden esperarse niveles reducidos de diversidad genética en este genoma (Zhan et al, 2011).…”
Section: Discussionunclassified